A risk adjusted cost‐effectiveness analysis of alternative models of nurse involvement in obesity management in primary care12. (16th April 2013) - Karnon, J.; Afzali, H. Haji Ali; Gray, J.; Holton, C.; Banham, D.; Beilby, J.
Abstract Objective: Controlled evaluations are subject to uncertainty regarding their replication in the real world, particularly around systems of service provision. Using routinely collected data, we undertook a risk adjusted cost‐effectiveness (RAC‐E) analysis of alternative applied models of primary health care for the management of obese adult patients. Models were based on the reported level of involvement of practice nurses (registered or enrolled nurses working in general practice) in the provision of clinical‐based activities. Design and Methods: Linked, routinely collected clinical data describing clinical outcomes (weight, BMI, and obesity‐related complications) and resource use (primary care, pharmaceutical, and hospital resource use) were collected. Potential confounders were controlled for using propensity weighted regression analyses. Results: Relative to low level involvement of practice nurses in the provision of clinical‐based activities to obese patients, high level involvement was associated with lower costs and better outcomes (more patients losing weight, and larger mean reductions in BMI). Excluding hospital costs, high level practice nurse involvement was associated with slightly higher costs. Incrementally, the high level model gets one additional obese patient to lose weight at an additional cost of $6, 741, and reduces mean BMI by an additional one point at an additional cost of $563 (upper 95% confidence interval $1, 547). Conclusion: Converted to quality adjusted life year (QALY) gains, the results provide a strong indication that increased involvement of practice nurses in clinical activities is associated with additional health benefits that are achieved at reasonable additional cost. Dissemination activities and incentives are required to encourage general practices to better integrate practice nurses in the active provision of clinical services.